High Light-Induced Nitric Oxide Production Induces Autophagy and Cell Death in Chlamydomonas reinhardtii - Kuo, Eva YuHua; Chang, Hsueh-Ling; Lin, Shu-Tseng; Lee, Tse-Min (Frontiers in Plant Science, 2020)
Autophagy plays a role in regulating important cellular functions in response to stress condition. The role of NO on the regulation of autophagy in Chlamydomonas reinhardtii has been not examined. Illumination of C. reinahrdtii cells under high light (HL, 1,600 μmol∙m-2∙s-1) condition elicited nitric oxide (NO) burst through the NO synthase- and nitrate reductase-independent routes and cell death. The abundance of CrATG8 protein, an autophagy marker of C. reinhardtii, increased after HL illumination along with a linear increase in the transcript abundance of autophagy-associated genes (CrVPS34, CrATG1, CrATG3, CrATG4, CrATG6, CrATG7, CrATG8, CrATG12), which were suppressed in the presence of a NO scavenger, 2-(4-carboxyphenyl)-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide (cPTIO). Cells were treated with NO donors, S-nitroso-N-acetyl-penicillamine (SNAP) and S-nitrosoglutathione (GSNO), under normal light (NL, 50 μmol∙m-2∙s-1) condition to elucidate the role of NO on autophagy activation and cell death. Treatment of 0.05 mM or 0.1 mM NO donors increased ATG8 protein and CrATG transcript abundances, which were suppressed in the presence of cPTIO. Moreover, treatment with 0.05 mM NO donors did not affect cell viability while 0.1 mM NO donors elicited a transient decrease in cell growth and death and recovered after 12 h, in which the transient effect can be prevented in the presence of cPTIO. However, the treatment of 1 mM H2O2 with 0.1 mM NO donors enhanced autophagy induction and resulted in cell death after 24 h culture. The interaction of H2O2 and NO can be prevented by cPTIO treatment. It reflects that NO is critical for the interaction of H2O2 and NO on cell death and autophagy induction. Further, the exposure of 0.1 mM NO donors under non-lethal HL condition (750 μmol∙m-2∙s-1) evoked autophagy and cell death. In conclusion, the present findings demonstrated that the NO-mediated autophagy pathway is activated in C. reinhardtii under lethal high intensity illumination and may interact with H2O2 for HL-induced cell death. The relationships between autophagy and cell death are discussed.